A Critical Discourse Analysis Anas Urbaningrum’s Representation In The Hambalang Case In Five Articles Of The Jakarta Post - Peberiwati br Kaban (Jurnal Scientia, 2024)
This research entitles "Anas Representation's Representation in the Hambalang Case in Four Articles of The Jakarta Post”. The Hambalang case is a big corruption in Indonesia and many high-figure politicians get involved, including Anas Urbaningrum (AU) as a former chairman Democratic Party. The study is aimed to demonstrate the social practice of AU’s representation and the way of AU’s representation related to the Hambalang case in the four articles of The Jakarta Post as well as to reveal the hidden ideology when representing AU. To achieve the aim of the research, the theory of critical discourse analysis (CDA) by Fairclough (1989, 1995b, and 2010), Transitivity system by Halliday&Matthiessen (2004) and the notion of the representation of social actor by Van Leeuwen (2008) are applied. The results of the study show that based on the types of process, the AU’s representation tends to be negative in the material clause, mental clause, relational clause, verbal clause, and existential clause. In contrast, the Corruption Eradication Commission (KPK) is portrayed prominently in positive way with the implementation of exclusion and impersonalization. With respect to ideology, The Jakarta Post, remains focus on Pancasila democracy that grounds to values of God-centered belief, humanity with freedom and equality spirit, unity of diverse society, mutual assistance, and social justice. Through the four texts, The Jakarta Post reproduces its ideology to sustain its relationship with the KPK as Our group (anti-corruption side) in order to combat corruptions issues in Indonesia and categorizes AU as Their group (corruptors’ side).